2022
DOI: 10.1002/adhm.202201740
|View full text |Cite
|
Sign up to set email alerts
|

A Biodegradable Metal‐Polymer Composite Stent Safe and Effective on Physiological and Serum‐Containing Biomimetic Conditions

Abstract: The new-generation coronary stents are expected to be biodegradable, and then the biocompatibility along with biodegradation becomes more challenging. It is a critical issue to choose appropriate biomimetic conditions to evaluate biocompatibility. Compared with other candidates for biodegradable stents, iron-based materials are of high mechanical strength, yet have raised more concerns about biodegradability and biocompatibility. Herein, a metal-polymer composite strategy is applied to accelerate the degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…We employed the mold casting method to fabricate the patterned surfaces, as schematically presented in Figure S2, and the topography was controlled with varied array parameters, in particular, heights and diameters. Here, we choose PLLA as the raw material because PLLA as well as its copolymer such as poly­(lactide- co -glycolide) (PLGA) is a kind of polymeric biomaterials widely used in biodegradable implants, and we choose human umbilical vein endothelial cells (HUVECs) as the model cell type because this is an important cell type widely used in biomaterial studies, in particular for cardiovascular systems. Roughness, plateau coverage, stereo coverage, and overall stiffness were calculated and correlated to adhesion behaviors of cells on different micropatterns. It is verified that these important parameters can semi-quantify the effects of surface topography on cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the mold casting method to fabricate the patterned surfaces, as schematically presented in Figure S2, and the topography was controlled with varied array parameters, in particular, heights and diameters. Here, we choose PLLA as the raw material because PLLA as well as its copolymer such as poly­(lactide- co -glycolide) (PLGA) is a kind of polymeric biomaterials widely used in biodegradable implants, and we choose human umbilical vein endothelial cells (HUVECs) as the model cell type because this is an important cell type widely used in biomaterial studies, in particular for cardiovascular systems. Roughness, plateau coverage, stereo coverage, and overall stiffness were calculated and correlated to adhesion behaviors of cells on different micropatterns. It is verified that these important parameters can semi-quantify the effects of surface topography on cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned results indicated that SMEN had good histocompatibility and potential application value. Before ending our discussion of a ROS‐responsive exosome coating of nitinol for interventional stent, it seems worthy of noting the effect of serum proteins on ROS, pointed out very recently by Ding team in their assessment of the potential cytotoxicity during their research and development of the next‐generation biodegradable cardiovascular device for interventional treatment along with the first clinical case, [ 73 ] based on their new concept of metal–polymer composite stent. [ 74 ] Both of their in vitro and in vivo examinations support the strong effects of physiological conditions, in particular serum proteins, on biocompatibility of an implant.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of biomaterials [ 48–53 ], the biodegradable type has been the front of medical devices [ 54–57 ], and some corrodible metals have been tried as the skeletal materials [ 58–60 ]. Even a metal-polymer composite stent has been into clinical research [ 61 , 62 ]. Our equation is expected to be a new tool to investigate biodegradable medical devices and assist the evaluation and choice of the biomaterial.…”
Section: Disscusionmentioning
confidence: 99%